Incidence and risk factors for major infections in hospitalized children with nephrotic syndrome - Kumar, Manish (J Bras Nefrol, 2019)
INTRODUCTION: Children with nephrotic syndrome are at increased risk of infections because of disease status itself and use of various immunosuppressive agents. In majority, infections trigger relapses requiring hospitalization with increased risk of morbidity and mortality. This study aimed to determine the incidence, spectrum, and risk factors for major infections in hospitalized children with nephrotic syndrome. METHODS: All consecutive hospitalized children between 1-12 years of age with nephrotic syndrome were enrolled in the study. Children with acute nephritis, secondary nephrotic syndrome as well as those admitted for diagnostic renal biopsy and intravenous cyclophosphamide or rituximab infusion were excluded. RESULTS: A total of 148 children with 162 admissions were enrolled. Incidence of major infections in hospitalized children with nephrotic syndrome was 43.8%. Peritonitis was the commonest infection (24%), followed by pneumonia (18%), urinary tract infection (15%), and cellulitis (14%), contributing with two thirds of major infections. Streptococcus pneumoniae (n = 9) was the predominant organism isolated in children with peritonitis and pneumonia. On logistic regression analysis, serum albumin < 1.5gm/dL was the only independent risk factor for all infections (OR 2.6; 95% CI, 1.2-6; p = 0.01), especially for peritonitis (OR 29; 95% CI, 3-270; p = 0.003). There were four deaths (2.5%) in our study, all due to sepsis and multiorgan failure. CONCLUSIONS: Infection remains an important cause of morbidity and mortality in children with nephrotic syndrome. As Pneumococcus was the most prevalent cause of infection in those children, attention should be paid to the pneumococcal immunization in children with nephrotic syndrome.